Ini Jenis-Jenis Tumbuhan Mangrove Di Kawasan Ekowisata Mangrove Kolam Susuk Kabupaten Belu: Jenis-jenis Tumbuhan Mangrove - Viennye Wilhelmina Djawa; Emilianus Pani; Chatarina G. Semiun (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Mangroves are a type of plant found in tropical coastal vegetation communities, which have large and broad potential benefits for the stability of a coastal ecosystem. In general, in a mangrove ecosystem area there are 2 (two) types of mangrove plants, namely true mangroves and associated mangroves. This research aims to find out about the types of mangrove plants and environmental conditions in the Susuk Pond mangrove ecotourism area, Belu Regency. The method used in this research is the Purposive Sampling method, namely determining stations by looking at the tidal zone and the mangrove growth substrate. Data collection at 3 (three) observation stations, namely Station 1 (S1), Station 2 (S2) and Station 3 (S3). The data collection method uses the roaming method. The data taken is data on mangrove plant types, abiotic parameter data and biotic parameter data. The data that has been collected is analyzed qualitatively descriptively. The results of the research show that in the Susuk Pond mangrove ecotourism area, Belu Regency, 23 (twenty-three) types of mangrove plants were found, consisting of 17 (seventeen) types of true mangroves and 6 (six) types of secondary mangroves. The types of true mengrove plants are Acanthus ebracteatus, Aegiceras floridum, Avicennia alba, Avicennia officinallis, Bruguiera cylindrica, Bruguiera gymnorrhiza, Bruguiera parviflora, Bruguiera sexangula, Ceriops tagal, Excoecaria agallocha, Laguncularia racemosa, Lumnitzera racemosa, Rhizophora apiculata, Rhizophora mangle, Rhizophora mucronata, Rhizophora stylosa, and Sonneratia alba. Meanwhile, the following types of mangrove plants are Celtis tenuifolia, Opuntia rastrera, Pandanus odorattisima, Pandanus tectorius, Pisticia vera, and Vitex trifolia. Environmental conditions, namely water temeparature ranging from 29?C-34?C, water temperature ranging from 28,5?C-32?C, sandy and mudy substrates, salinity ranging from 0,97 ?/oo-3,73 ?/oo, pH ranging from 6,95-7,23, condutivity ranging from 17,3 ?s/cm-84,4 ?s/cm and TDS ranging from 15,3 ppm-93,6 ppm. The range of environmental and water quality parameter valuases, if associated with the ideal water quality range for the growth and survival of mangrove plants of marine biota are in ideal conditions or can still be tolerated for growth and survival.